2010
DOI: 10.1111/j.1742-4658.2010.07751.x
|View full text |Cite
|
Sign up to set email alerts
|

New members of the brachyurins family in lobster include a trypsin‐like enzyme with amino acid substitutions in the substrate‐binding pocket

Abstract: Crustacean serine proteases (Brachyurins, EC 3.4.21.32) exhibit a wide variety of primary specificities and no member of this family has been reported for spiny lobsters. The aim of this work was to study the diversity of trypsins in the digestive gland of Panulirus argus. Several trypsin-like proteases were cloned and the results suggest that at least three gene families encode trypsins in the lobster. Three-dimensional comparative models of each trypsin anticipated differences in the interaction of these enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…GU338026), PaTry2 (GU338028), PaTry3 (GU338029) and PaTry4 (GU338030). Specific primers (Biomers.net, Ulm, Germany) used for lobster trypsins were successfully employed before (Perera et al, 2010a) and are shown in Table2. The efficiency of target amplification for each primer set was optimized in the previous study by using 4pmoll -1 of primers and 60°C of annealing/extension (Perera et al, 2010a); thus, these conditions were employed here.…”
Section: Trypsin Expression By Rt-qpcrmentioning
confidence: 99%
See 4 more Smart Citations
“…GU338026), PaTry2 (GU338028), PaTry3 (GU338029) and PaTry4 (GU338030). Specific primers (Biomers.net, Ulm, Germany) used for lobster trypsins were successfully employed before (Perera et al, 2010a) and are shown in Table2. The efficiency of target amplification for each primer set was optimized in the previous study by using 4pmoll -1 of primers and 60°C of annealing/extension (Perera et al, 2010a); thus, these conditions were employed here.…”
Section: Trypsin Expression By Rt-qpcrmentioning
confidence: 99%
“…Specific primers (Biomers.net, Ulm, Germany) used for lobster trypsins were successfully employed before (Perera et al, 2010a) and are shown in Table2. The efficiency of target amplification for each primer set was optimized in the previous study by using 4pmoll -1 of primers and 60°C of annealing/extension (Perera et al, 2010a); thus, these conditions were employed here. By means of calibration curves (10-fold dilutions, corresponding to cDNA in reactions from 20ng to 0.2pg) all primer pairs were checked to produce similar efficiencies, except PaTry4.…”
Section: Trypsin Expression By Rt-qpcrmentioning
confidence: 99%
See 3 more Smart Citations